THE ANALYSIS ON FACTORS INFLUENCING COSTUMERS TO DO SHOPPING AT SRIRATU SUPERMARKET PEMUDA BRANCH SEMARANG - Puspitasari, Mayranni Rizky; Suryoko, Sri; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Along with the rise of people's daily need, numbers of small retail start to grow with its own characteristics. It results in a tight competition among retail outlets. To win the competition so that it won't be left by the consumers, those small retail should understand and fill the consumer's needed. One of the small retail in Semarang is Pasaraya Sri Ratu Pemuda Semarang. But nowadays in line with the increasing number of small retail it causes the decreasing of sales of Sri Ratu Pemuda year by years.The objective of this research is find out the influencing factors for consumers to shop at Pasaraya Sri Ratu Pemuda Semarang. This research used exploratory research. The technique of sampling is nonprobability sampling and incidental sampling. The sample of this research is about 100 people who visited and shopped at Pasaraya Sri Ratu Pemuda Semarang. The measurements scale used Likert scale. SPAS 20.0 is also used to help the analysis.For the result, it can be seen that the factor which influence the costumers to shop at Pasaraya Sri Ratu Pemuda Semarang include of price, product, location, service quality and other factors. The price factor variable is divided into two, they are primary price factor and secondary price factor. The product factor variable is divided into two, they are the main factor and product attribute factor. The location variable in this research analysis is getting reduced so one of the remaining factor is safety and location comfort factor. The service quality variable is divided into four factors, they are the ability of workers in giving service , the communication ability with consumer, physical and supporting facilities factor. The other variable is divided into two, they are utilitarian value and hedonic value.It is suggested that the company pay attention for some factors such as pricing strategy, providing variety of product line, increasing the service quality and supporting facilities so that the consumers feel comfortable in shopping.